Tar baby - Morrison, Toni. (New York, N.Y. : Plume, 1982)
A beautiful African-American woman of privilege finds herself attracted to the kind of man she has dreaded since childhood: uneducated, violent, and contemptuous of her.
"A Plume book.".
Booklist.
Library Journal.
Wilson's Fiction.
Young Adult
Keywords: African Americans -- Race identity -- Fiction; Interpersonal relations -- Fiction; African Americans -- Race identity -- Fiction; Interpersonal relations -- Fiction; Love stories; Love stories